The Measurement of Social Exclusion - Conchita D'Ambrosio; Satya R. Chakravarty (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper develops an axiomatic approach to the measurement of social exclusion. At the individual level, social exclusion is viewed in terms of deprivation of the person concerned with respect to different functionings in the society. At the aggregate level we treat social exclusion as a function of individual exclusions. The class of subgroup decomposable social exclusion measures using a set of independent axioms is identified. We then look at the problem of ranking exclusion profiles by exclusion dominance principle under certain restrictions. Finally, applications of decomposable and non-decomposable measures suggested in the paper using European Union and Italian data are also considered.
Keywords: D63; 330; Social Exclusion; Axioms; Characterization; Dominance; Application; Policy; Soziale Isolation; Messung; Disparitätsmass; Theorie